Effect of supplementation of purslane/Portulaca oleracea in hyperglycemic subjects - Tarkergari, S.; Waghray, K.; Gulla, S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Portulaca oleracea (Purslane) is an annual succulent medicinal plant grown all over the world containing diverse phytoconstituents. Several studies have reported its pharmacological effects like antihypertensive, anti-inflammatory, antioxidant, hypoglycemic, hypocholesterolemic, hypotriglyceridemic, neuro, hepato and nephro protective effects. Methods: Dried Portulaca oleracea leaves were incorporated into common food adjunct popularly known as karampodi/spice powder in south India. This spice powder was used for supplementation studies for 90 days (3months) among hyper glycemic subjects after obtaining a written informed consent. Biochemical parameters such as fasting, post lunch blood glucose levels, glycosylated hemoglobin, lipid profile, i.e., total cholesterol, low density lipoprotein cholesterol, triglycerides, high density lipoprotein cholesterol, very low-density lipoprotein cholesterol, kidney function test, liver function test were assessed. Baseline information, their medical history and 24-hour dietary recall was elicited from the subjects through a pretested schedule. Results: The results revealed that fasting, post lunch blood glucose levels, glycosylated hemoglobin, the total cholesterol levels and its fractions along with triglycerides were significantly decreased and HDL-C increased significantly in the test groups from pre-supplementation to during-supplementation and was stable at post-supplementation period. Conclusions: The results indicated that the spice powder which was rich in several polysaccharides, polyunsaturated fatty acids and phytochemicals/phytonutrients when supplemented to hyperglycemic subjects had a strong hypoglycemic, hypocholesterolemic and hypotriglyceridemic effect.